2014
DOI: 10.1189/jlb.3ab0414-216r
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 and TLR7/8 activation induces formation of keratic precipitates and giant macrophages in the mouse cornea

Abstract: Macrophage adherence to the inner corneal surface and formation of MGCs in the stroma are common signs of chronic inflammation following corneal infection. To determine whether macrophage adherence (known clinically as KPs) and giant cell formation were specific to innate immune activation via particular TLR ligands, macrophage activation was examined in a murine model of TLR-mediated corneal inflammation. The corneal epithelium was debrided and highly purified TLR ligands were topically applied once to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
2
23
0
Order By: Relevance
“…The observed morphologic changes in endothelial cells at 1 week are independent of the presence of keratic precipitates and activated stromal macrophages, which are a known feature of corneal inflammation in response to CpGtreatment. 13 For all conditions, the absolute degree of endothelial cell hexagonality was unchanged, supporting the concept that polymegethism is a more sensitive index of corneal endothelial responses to inflammation/injury than the degree of hexagonality (pleomorphism). 16 We recently reported the presence of large, multinucleated giant macrophages in the mouse cornea 1 week after CpG-ODN treatment; however, this was not associated with any overt corneal endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…The observed morphologic changes in endothelial cells at 1 week are independent of the presence of keratic precipitates and activated stromal macrophages, which are a known feature of corneal inflammation in response to CpGtreatment. 13 For all conditions, the absolute degree of endothelial cell hexagonality was unchanged, supporting the concept that polymegethism is a more sensitive index of corneal endothelial responses to inflammation/injury than the degree of hexagonality (pleomorphism). 16 We recently reported the presence of large, multinucleated giant macrophages in the mouse cornea 1 week after CpG-ODN treatment; however, this was not associated with any overt corneal endothelial dysfunction.…”
Section: Discussionsupporting
confidence: 55%
“…16 We recently reported the presence of large, multinucleated giant macrophages in the mouse cornea 1 week after CpG-ODN treatment; however, this was not associated with any overt corneal endothelial dysfunction. 13 In the present study, intact ZO-1 expression, normal CCT, and normal ECD were observed in all groups at 1 week post treatment; however, there was reduced ECD and increased CCT at 4 weeks after CpG-ODN treatment. These signs of corneal pathology in the CpG-ODN-treated group were associated with the presence of enlarged CD45 þ cells throughout the corneal stroma, indicating persistent activation of inflammatory cells.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations